Expectation Causes Misperception of the Attitude Indicator in Nonpilots: A Fixed-Base Simulator Experiment. (February 2020) - Landman, Annemarie; Groen, Eric L.; van Paassen, M. M. (René); Bronkhorst, Adelbert W.; Mulder, Max
Previous studies show that pilots sometimes make roll reversal errors (RREs) when responding to the aircraft bank angle shown on the attitude indicator (AI). This is suggestive of a perceptual ambiguity in the AI. In the current study, we investigated whether expectation contributes to such misperception. Twenty nonpilots performed tasks in a fixed-base flight simulator. Their expectation about the bank angle was manipulated with a flying task using outside view only. When flying at a bank angle, the outside view disappeared, a moving-horizon type AI was shown, and participants had to roll the wings level, trusting the AI. The AI often matched the previously flown turn. However, in some runs, it showed an opposite bank direction (Opposite condition), which was hypothesized to facilitate a misperception. In some other runs, it showed level flight (Level condition), which should not facilitate this. In a second session, participants rolled wings level without preceding flying task (Baseline condition). Participants made 11.2 times more RREs in the Opposite condition (75% error rate) compared to Baseline condition (6.7%), and 2.5 times more compared to the Level condition (30%). This indicates that RREs were in many cases caused by expectation-induced misperception of the AI bank angle.